In the aftermath of the Palestinian parliamentary elections: How to deal with Hamas? - Muriel Asseburg (Stiftung Wissenschaft und Politik (SWP), 2006)
Following its unexpected landslide victory in the elections on January 25, 2006, Hamas will hold an absolute majority in the Palestinian Legislative Council (74 of 132 seats). After the result was announced, Hamas - which contested the election as a party under the name of 'Change and Reform' - announced that it was ready to take on the responsibility of government and work together with other political forces. Accordingly, it has entered negotiations with possible coalition partners over policy positions and the distribution of posts. For a grouping that has only just decided to work within the political system - and had expected to occupy the role of a strong opposition - this represents an enormous challenge. The Fatah membership's disappointment over the defeat exploded in violent clashes, which contain great potential for escalation. (SWP Comments / SWP)
Keywords: 320